PENGARUH DIRECT MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN THE CENTRUM BANDUNG - Purnama, Ridwan; Pralina, Alfania Riska (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
The tourism industry is one sector of the economy, is also part of the national development of a nation. Tourism has an effect on the economy of the tourist destination. Indonesia is an archipelago with attractive tourism resources, both natural beauty and variety cultural. Bandung is a city that is always visited by tourists. With the number of tourists coming necessarily have to be balanced with adequate supporting tourism facilities as well as restaurants. The Centrum is one restaurant that has a feel like a cruise ship, to be able to compete with other restaurants The Centrum strive to meet the wishes and needs of guests. The number of purchases at the restaurant The Centrum experiencing fluctuating so does the amount of income. Strategies under taken in improving the purchasing decision one of them is Direct Marketing. This study aimed to obtain findings on direct marketing, purchasing decisions and influence between the two at the restaurant The Centrum. This type of research is descriptive and verification method used is explanatory survey. The sample of 100 respondents with a sampling technique that is systematic random sampling. Data analysis technique used is multiple regression analysis. The independent variable in this study is face to face selling (X1), telemarketing (X2) and online marketing (X3) while the dependent variable is the purchase decision (Y). The results showed that the respondents about direct marketing is generally considered high. There biggest influence on online marketing while telemarketing received the lowest ratings. Responder regarding the purchasing decisions rated. The indicator that received the highest score is the method of payment and that got the lowest score is the number of purchases. Based on testing SPSS 20 shows a correlation between the partial simultaneous and direct marketing to the purchase decision.